Phraseology and Set Phrases in Albanian Language - Miconi, Harallamb (Mediterranean Journal of Social Sciences, 2012)
The new approach, in Albanian linguistics, concerning the phrase (sintagmÃ«, in Albanian) consisting of two or more whateversuccessive elements as the minimal syntactic unit instead of the â€œword-groupâ€ (togfjalÃ«sh, in Albanian) consisting of at least two contentwords is of great interest to the field of phraseology as well. Researching in this frame, we adopt the set phrase theory for the multiwordstructure on which phraseology should be based. In our research in the field of phraseology, we consider the importance of the (set)phrase in justifying some cases which are accepted as idioms (phraseological unit, in Albanian), such as the idioms vret e pret =[he,she] is brutal (kills and destroys, lit.), varg e vistÃ«r, zhyt e mbyt, flakÃ« e flakÃ«, etc. which are expressed through coordinated relationsand which, as a result, are not justified by the word-group theory that is defined as subordinated relation of content words. We considerthe importance of the phrase even in revealing other cases of multiword units, such as nÃ« tym = without thinking (in smoke, lit.), mespec, me bisht, etc. expressed by prepositional phrases or e piu = [he,she] had a bad end (drank it, lit.), e qau; i dhashÃ« njÃ« (nÃ« kokÃ«),etc. expressed by phrases one component of which is not a content word, but a pronoun or a numeral, and which should be accepted asidioms.